Turner the extraordinary life and momentous times of J.M.W. Turner - Moyle, Franny 1964- (Penguin Books, 2017)
The extraordinary life of J.M.W Turner, one of Britain's most admired, misunderstood and celebrated artists. Turner is Britain's most famous landscape painter. Yet beyond his artistic achievements, little is known of the man himself and the events of his life: the tragic committal of his mother to a lunatic asylum, the personal sacrifices he made to effect his stratospheric rise, and the bizarre double life he chose to lead in the last years of his life. A near-mythical figure in his own lifetime, Franny Moyle tells the story of the man who was considered visionary at best and ludicrous at worst